2021
DOI: 10.3390/cells10112957
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on miRNAs Targeting DKK1 for Developing Hair Regeneration Therapy

Abstract: Androgenetic alopecia (AGA) remains an unsolved problem for the well-being of humankind, although multiple important involvements in hair growth have been discovered. Up until now, there is no ideal therapy in clinical practice in terms of efficacy and safety. Ultimately, there is a strong need for developing a feasible remedy for preventing and treating AGA. The Wnt/β-catenin signaling pathway is critical in hair restoration. Thus, AGA treatment via modulating this pathway is rational, although challenging. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 230 publications
2
14
0
Order By: Relevance
“…Wnt/β-catenin signaling pathway plays an important role in regulating hair growth and entry into the anagen phase [ 38 , 39 , 40 ]. Dickkopf-related protein 1 (DKK1), a natural inhibitor of Wnt, strongly suppresses the Wnt/β-catenin signaling pathway [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt/β-catenin signaling pathway plays an important role in regulating hair growth and entry into the anagen phase [ 38 , 39 , 40 ]. Dickkopf-related protein 1 (DKK1), a natural inhibitor of Wnt, strongly suppresses the Wnt/β-catenin signaling pathway [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signaling pathway plays an important role in regulating hair growth and entry into the anagen phase [ 38 , 39 , 40 ]. Dickkopf-related protein 1 (DKK1), a natural inhibitor of Wnt, strongly suppresses the Wnt/β-catenin signaling pathway [ 40 ]. Zhang et al [ 9 ] showed that the transcript levels of 5α-reductase type 1 ( SRD5A ), AR , and DKK1 were greatly reduced in Fgf5 KO sheep, suggesting a close relationship between FGF5 signaling and AR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Argonaute (AGO) protein family recognizes miRNA and leads to the loading of miRNA guide strand into the RNA-induced silencing complex (RISC). The passenger strand is degraded and approximately 22 nucleotide-length miRNA containing seed region is ready to bind the specific region of the target messenger RNA (mRNA) molecule on the 3’untranslated region (3’UTR) that consequently leads to the silencing of the target gene ( 22 , 28 ). Remarkably, miRNAs are implicated in the regulation of key pathways that are usually genetically altered in various cancers.…”
Section: Mirna Role In Cancersmentioning
confidence: 99%
“…Currently, over 3000 miRNAs are found in almost all human body fluids. These miRNAs are implicated in various processes and play a significant role in the progression or regression of a number of diseases (22)(23)(24)(25)(26). miRNAs vary in their function as they have a strong capacity of regulating multiple gene expression.…”
Section: Mirna Role In Cancersmentioning
confidence: 99%
“…The DKK1 and Wnt/β-catenin regulation are critical approaches in promoting hair growth. Papukashvili et al reviewed the miRs (e.g., miR-103/107, miR-203, and miR-218) that could modulate the Wnt/β-catenin signaling pathway via regulating DKK1 and represent attractive therapeutic candidates [9]. Recent studies have shown the role of miRs in the pathogenesis of inflammatory bowel disease.…”
Section: Group Of Mirsmentioning
confidence: 99%